The Key To Success To Optimal Employee Performance Through Quality Of Work Life - Darmawan, Kusnanto (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
Employee performance encompasses an individual's proficiency, skills, and job outcomes demonstrated while fulfilling their work duties and responsibilities. Evaluating employee performance involves assessing the attainment of predefined objectives, overall work productivity, the caliber of work outcomes, and collaborative effectiveness within the team. This study aims to explore the impact of Quality of Work Life (QWL) and work motivation on the performance of sub-district employees in Lumajang Regency. Employing descriptive and causal research methods, primary data were gathered through interviews and questionnaires distributed to 100 respondents, complemented by secondary data in the form of agency documents. The sample collection utilized a simple saturated technique, and the data analysis employed multiple linear regression. The partial findings indicate a positive and noteworthy influence of Quality of Work Life (QWL) and work motivation on employee performance. The R Square value, at 0.531, signifies that these variables collectively contribute to 53.1% of the variance in employee performance, with the remaining 46.9% potentially influenced by other factors like Organizational Citizenship Behavior (OCB), commitment, and satisfaction.